Transfer of Economic Rights of the Author of Works Represented into NFT by Smart Contract - Andrade, Timothy Arviando; Hakim, Irfan (Pandecta Research Law Journal, 2024)
This research analyzes intellectual property law in relation to the transfer of economic rights from the author of the intellectual creation represented into the Non-Fungible Token (NFT) to the NFT buyer by a smart contract. The purpose of this research is to examine and comprehend the transfer of economic rights from the author of the intellectual creation represented into the NFT to the NFT buyer by a smart contract. This research approaches the topic from legal perspective, using the normative juridical method. This research will closely examine several relevant the provisions of laws and regulations to identify and analyze the legal issues involved in the transfer of economic rights from the author of the intellectual creation represented into the NFT to the NFT buyer by a smart contract. Research has shown that Article 16 Paragraph (2) of the Copyright Law can be applied to the transfer of economic rights of intellectual creation represented into the NFT by a smart contract, using the argumentum per analogiam method. This means that NFT buyer can enjoy the economic rights listed in Article 9 Paragraph (1) the Copyright Law.